Interaction between Pheromone and Its Receptor of the Fission Yeast Schizosaccharomyces pombe Examined by a Force Spectroscopy Study. (21st February 2012) - Sasuga, Shintaro; Abe, Ryohei; Nikaido, Osamu; Kiyosaki, Shoichi; Sekiguchi, Hiroshi; Ikai, Atsushi; Osada, Toshiya
Abstract : Interaction between P-factor, a peptide pheromone composed of 23 amino acid residues, and its pheromone receptor, Mam2, on the cell surface of the fission yeast Schizosaccharomyces pombe was examined by an atomic force microscope (AFM). An AFM tip was modified with P-factor derivatives to perform force curve measurements. The specific interaction force between P-factor and Mam2 was calculated to be around 120 pN at a probe speed of 1.74 μ m/s. When the AFM tip was modified with truncated P-factor derivative lacking C-terminal Leu, the specific interaction between the tip and the cell surface was not observed. These results were also confirmed with an assay system using a green fluorescent protein (GFP) reporter gene to monitor the activation level of signal transduction following the interaction of Mam2 with P-factor.